Microcell parasites of molluscs: introduction to DAO Special 7 - Carnegie, RB; Engelsma, MY (Diseases of Aquatic Organisms, 2014)
First discovered decades ago, microcell protistan parasites of the genera Bonamia and Mikrocytos remain relevant today for their economic impacts on growing molluscan aquaculture industries and fisheries. Bonamia parasites have received more attention over the years in part because they are more widespread and thus of wider concern, but there has been renewed interest in Mikrocytos recently with the generation of important new findings. Among these has been the surprising observation that Mikrocytos has phylogenetic affinities to the Rhizaria, which includes the haplosporidian protists and the genus Bonamia. This Diseases of Aquatic Organisms Special, emerging from the 5th Meeting of the Microcell Working Group held at the Central Veterinary Institute, Lelystad, the Netherlands, in February 2012, presents new insights into Mikrocytos and Bonamia diversity, distributions, diagnostics, ultrastructure, and infection dynamics, and captures major developments in the field since the last review of these genera in 2004.